Family Characteristics and Social Functioning Associated with Duration and Frequency of Child Sexual Assault - Adi Fahrudin; Durin Edward; Husmiati Yusuf; Wan Anor Wan Sulaiman; Mohd Dahlan Hj Malek (2018)
This study reports the sexual abuse of children in Sabah, Malaysia. The objective of this study is to analyze the relationship between family characteristics and social functioning associated with the duration and frequency of sexual assault on the child survivors. Eighty children who reported sexual assault through a One Stop Crisis Centre in an urban hospital were studied. The main research instrument used was adapted from the Inner Interaction Scale of Social Functioning (IISSF). The results of the study show that there are significant differences in the social functioning of victims according to the frequency of sexual assault, but not according to the duration of assault. That is the social functioning symptoms of achievement and expectation was significantly different according to the frequency of sexual assault. The relationship of the variable’s family characteristics, frequency and duration of sexual assault as well as the social functioning of the victims is important for social workers both to understand and to take note of in intervention work with child sexual assault survivors who report their abuse. The implications of these findings were also discussed in the context of the provision of crisis intervention support for child victims of sexual assault by social workers in Malaysia.